“It’s a great place for kids!”: the settlement of Ma’ale Adumim as a suburban safe space - Allegra, Marco (2019)
The status of Jerusalem is almost universally regarded as the single most divisive issue in Israeli-Palestinian relations; and Israel’s settlement policy – and its territorial and demographic implications – is widely considered as the most significant “fact on the ground” established by Israel since 1967. We address these issues by observing how Israel’s settlement policy in the area of metropolitan Jerusalem transformed the material, symbolic and political landscape of Israeli-Palestinian relations. Through the case study of the settlement of Ma’ale Adumim, this paper focuses on settlers’ place attachment, personal geographies, and the relation between the latter and the production of space. We maintain that the “suburban experience” embodied in the lives of the residents illustrates the action of powerful drivers of the overall process of normalization of Jewish presence in the West Bank; in turn, this rendered the settlement policy relatively uncontroversial for large sectors of Israeli public opinion. Also, we maintain that settlements such as Ma’ale Adumim are also the product of the quest for a suburban “safe space” – i. e. an enclosed space designed to avoid contacts with “unpleasant otherness” that residents of the suburbs all over the world often associate to life in the inner city.